Effects of Dietary Supplementation with Turmeric and Ginger on Growth Performance and Antioxidant Enzyme Status in Pig - Bhargav, Kakumanu; Reddy, Lingamdinne Siva Sankar Varaprasad; Naik, Bonath Rambabu; Sivakumar, Avadhanam Venkata Naga; Chakravarthi, Matha Kalyana (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This research was aimed to evaluate the effect of dietary supplementation of turmeric and ginger @ 1% on the body weight on antioxidant  profile in SVVU T-17 grower pigs. The study conducted over 60 days evaluated 72 SVVU T-17 crossbred grower pigs, which were divided  into three groups. C (Control) group received only basal diet (as per NRC, 2012); T group supplemented with Turmeric @ 1% in basal diet  and G group supplemented with Ginger @ 1% in basal diet. Results demonstrated that the treatment group T (42.33±0.91 kg) exhibited  significantly higher mean body weights (p
Keywords: Antioxidant enzymes; Body weight; Ginger; Pig; Supplementation; Turmeric